A PAPER SURVEY ON THE IMPLEMENTATION OF THE PARALLEL FDTD ON MULTIPROCESSORS USING MPI - Adamu Abubakar Isah; Oyku Akaydin; Mehmet Kusaf (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The research work explains a cost-effective, highperformance computing platform for the parallel implementation of the FDTD algorithm on PC clusters using the message-passing interface (MPI) library, which is a local area network system consisting of multiple interconnected personal computers (PCs), and is already widely employed for parallel computing.